Health technology assessment through the six sigma approach in abdominoplasty: Scalpel vs electrosurgery. (July 2021) - Ricciardi, C.; Gubitosi, A.; Lanzano, G.; Parisi, S.; Grella, E.; Ruggiero, R.; Izzo, S.; Docimo, L.; Ferraro, G.; Improta, G.
Highlights: A health technology assessment between two incisions for abdominoplasty is performed. The DMAIC cycle of Six Sigma is used to compare the incisions through the drain output of patients. Statistical tests are computed, and Six Sigma tools are used to compare two groups of patients. This retrospective study shows some possible advantages of creating the skin incision in full abdominoplasty with a scalpel. A reduction in the total drain output and in wound dehiscence can be achieved by using scalpel rather than electrosurgery. Abstract: Abdominoplasty is a surgical procedure conducted to reduce excess abdominal skin and fat and improve body contouring. Despite being commonly performed, it is associated with a risk of complications such as infection, seroma, haematoma and wound dehiscence. To reduce the incidence of complications, different methods are used to create the abdominal flap, i.e., incision with a scalpel or electrosurgery. In this study, health technology assessment (HTA) using the Six Sigma methodology was conducted to compare these incision techniques in patients undergoing abdominoplasty. Two consecutively enroled groups of patients (33 in the scalpel group and 35 in the electrosurgery group) who underwent surgery at a single institution, the University of Campania "Luigi Vanvitelli", were analysed using the drain output as the main outcome for comparison of the incision techniques. While no difference was found regarding haematoma or seroma formation (no cases in either group), the main results also indicate a greater drain output (p-value<0.001) and a greater incidence of dehiscence (p-value=0.056) in patients whose incisions were made through electrosurgery. The combination of HTA and the Six Sigma methodology was useful to prove the possible advantages of creating skin incisions with a scalpel in full abdominoplasty, particularly a significant reduction in the total drain output and a reduction in wound healing problems, namely, wound dehiscence, when compared with electrosurgery, despite considering two limited and heterogeneous groups.